Інтеграційна ідея на Слов’янскому конгресі в Празі 1848 року - Бевзюк, Є. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2018)
У статті аналізується ідея австрославізму. Концептуального проекту, що був спрямований на інтеграцію народів Центрально-Східної
Європи. У результаті дослідження доведено, що в 30-х–40-х рр. XIX ст.
соціально строкаті та амбівалентні етнічні еліти енергійно й темпераментно спрямовували свій інтелект у площину теоретичних пошуків
рамок своєї ідентичності. Отже, будь-який публічний захід ставав
таким собі інтелектуальним майданчиком для апробації різних ідей.
Тому певною реакцією на «пришестя» до Європи націоналізму була
організація Слов’янського конгресу. Конгрес варто розглядати не як
масштабне європейське явище, а як одну зі складових у загальному ланцюгу зростаючого європейського націоналізму. На слов’янському зібранні чехи виступили з ідеєю федералістського австрославізму. Досить часто
сама ця ідея оцінювалася переважно як містечковий, регіональний
слов’яно-австрійський проект. Таку оцінку варто вважати дещо неповною. Матеріали конгресу підтверджують, що ідею австрославізму
варто вважати далекоглядним підходом до визначення майбутньої долі
об’єднаної Європи. Лише сьогодні європейська спільнота може зрозуміти, що у федералізмі був закладений новий ідейний зміст емансипації
монархії — здійснення наднаціональної побудови держави, яка в перспективі могла би стати моделлю загальноєвропейського значення. It is a historical fact that the objective conditions for the successful
practical implementation of the idea of regional European integration first
emerged in Central and Eastern Europe. However, the theoretical basis and
first practical attempts to uptake the ideas of European states unity have deep
historical roots, which should be taken into account in the study of modern
European integration processes. Each of the European actors (Germans,
Austrians, Czechs, Slovaks) has a unique historical experience of regional and
continental policies formation and implementation.
The first half of the 19th century was marked by the beginning of the active
national self-determination process of the peoples of Central and Southeast
Europe. At this stage of history traditions were being destroyed, nations began
to emerge, and Slavic politicians worked on the content of their national
projects. And the final result of many politicians’ plans of the Austrian Empire
was the construction of national states. In any case, the national ideologists’
positive attitude towards the idea of a civilized cultural unity of the peoples of
Europe remained unchanged. It was on its basis that the keystone of national
ideologies was built. Accordingly, the aim of the article has been to study the
idea of Austro-Slavism as the theoretical project of integration of the peoples
of Central and Eastern Europe.
The research has proved that in the 1830’s and 1840’s ethnic European
elites directed their intelligence towards the formation of their national and
cultural framework. Therefore the organization of the Slavic Congress in 1848
became a reaction to the national processes in Europe. The Congress should
be considered as one of the links in the overall chain of growing European
nationalism. At the Slavic Assembly the Czechs put forward the idea of
federalist Austro-Slavism.
The idea itself was quite often valued mainly as a small, regional Slavic-
Austrian project. Such an assessment should be considered as somewhat
incomplete. The materials of the Congress confirm that the idea of Austro-
Slavism should be considered as a promising concept in terms of determining
the future of the united Europe. European Thought, as part of a comprehensive
idea of the unity of European civilization, gradually became a spiritual
tradition that passed from generation to generation of the Slavic politicians.
The basis for numerous projects of the “United Europe” was laid. Only today
the European community can understand that a new ideological content of the
emancipation of the monarchy was laid in the federalist approach — the
implementation of a supranational construction of a state that in the long run
could be a model of Pan-European significance.